STRATEGI PEMUNGUTAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB P2) OLEH DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET DAERAH (DPPKAD) KOTA PAYAKUMBUH - Risky Annisa; Chalid Sahuri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Implementation of the strategy of land and building tax collection Rural and Urban Areas according to Regulation No. 14 of 2013 is a policy that aims to pursue and manage potential sector and Building Tax Rural and Urban in the region Payakumbuh. The phenomenon that occurs is that people are not informed about changes in the system for collection of the United Nations after the P2 is managed by the local government and the amount of the taxpayer who does not pay taxes in accordance with the specified time.The concept of the theories used by researchers is the theory Salusu strategy by explaining that the strategy is an art of using the skills and resources of an organization that is used to reach the final destination. The method used in the study includes observations and interviews on the implementing legislation and the owners of land and buildings / Taxpayers as well as documentation and literature study related to the research objectives.The results of the analysis that the implementation of the strategy of land and building tax collection Rural and Urban in Payakumbuh not been implemented because of the persistence of the determination of the structure and size of the tax rate, the procedure of voting and polling area, inspection and administrative sanctions that are not yet optimal. The factors that affect the implementation of the collection is the socialization of land and building tax Rural and Urban, community participation and infrastructure.Keywords: Strategy, Regional Regulation, Land and Building Tax Rural and Urban (PBB P2)